Analisis kreatif saluran pemasaran jamur tiram di kelurahan teratai - Uliya, Uliya; Armando, Reno; Lamefa, Dina Yuliasty; Enita (Journal of Creative Attitudes Culture, 2024)
The large demand for oyster mushrooms in the market makes business actors have great hopes of obtaining large income from oyster mushroom cultivation such as Pondok Jamur Endan. The objectives of this study are as follows: to determine the marketing strategy for oyster mushroom products. To determine the marketing strategy for oyster mushroom products. This study was conducted in Pondok Jamur Endang, Teratai Village, Muara Bulian District. The results of the marketing analysis study showed that the oyster mushroom marketing channels in Pondok Jamur Endang have four channels, namely channel I, namely oyster mushroom marketing from farmers - end consumers, channel II, namely oyster mushroom marketing from farmers - retailers - end consumers, channel III, namely oyster mushroom marketing from farmers - intermediaries - retailers - end consumers, and channel IV, namely oyster mushroom marketing from farmers - wholesalers - intermediaries - retailers - end consumers.